DAMPAK FLYPAPER EFFECT TERHADAP KEMISKINAN (STUDI KOMPARASI KOTA DENGAN KABUPATEN) - Khairy, Rahmat Nur; Susilo (Contemporary Studies in Economic, Finance and Banking, 2024)
Flypaper effect it’s a phenomenon, when a region's spending is more reactive to transfer funds than its own regional income. The purpose of this study is to examine and analyze the existence of the flypaper effect that occurs, and to find out whether Regional Expenditure is able to mediate income against poverty. By conducting a comparative study between regencies and cities in East Java Province in 2010-2019, using the Path Coefficient Regression method, it was found that there was no flypaper effect in cities, and there was a flypaper effect in regencies. On the other hand, in both cities and regencies, regional spending mediates income against poverty. However, the effect of PAD on poverty in cities tends to be greater, when compared to districts. Thus, in order to achieve the goal of fiscal decentralization towards self-sufficient local government funding, it is necessary to take steps to minimize the effect of the flypaper effect in the district area.